1974
DOI: 10.4049/jimmunol.113.2.608
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibody Formation by Human Tonsil Lymphocytes

Abstract: In vitro antibody formation by human lymphocytes was observed against hapten-protein conjugates by using human palatine tonsil cells in the presence of an optimum concentration of 2-mercaptoethanol. Relatively pure populations of B and T lymphocytes were prepared by the method of Ficoll-Hypaque gradient centrifugation to investigate cellular mechanism of antibody formation by human lymphocytes. Maximum response to hapten-protein conjugates was observed in vitro when T and B cells were mixed at an optimal ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Total mononuclear cell yields will range from 5 × 10 8 to 5 × 10 9 cells per pair of tonsils. B cells comprise 60% to 70% of the cell population after Ficoll-Hypaque centrifugation, while 30% to 40% are T cells and 1% to 8% are monocytes (Watanabe et al, 1974). Dendritic cells comprise <1% of the cell population (Hart and McKenzie, 1988).…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total mononuclear cell yields will range from 5 × 10 8 to 5 × 10 9 cells per pair of tonsils. B cells comprise 60% to 70% of the cell population after Ficoll-Hypaque centrifugation, while 30% to 40% are T cells and 1% to 8% are monocytes (Watanabe et al, 1974). Dendritic cells comprise <1% of the cell population (Hart and McKenzie, 1988).…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…Investigators in the early 1970s first separated tonsillar lymphocytes from stroma by gentle teasing with small-gauge needles, and showed that these cells could be stimulated in vitro to produce immunoglobulin if the ratios of T and B cells were adjusted appropriately (Hoffmann et al, 1973;Sloyer et al, 1973). Preparation of single-cell suspensions was facilitated by the passage of cells through a fine-mesh sieve (Watanabe et al, 1974). Today, tonsils are most often used as a source of large numbers of human B cells, which are often further separated by size using countercurrent centrifugation (Muraguchi et al, 1983), or into fractions of differing density on Percoll gradients (Nakagawa et al, 1988).…”
Section: Commentary Background Informationmentioning
confidence: 99%